Removable prosthodontic considerations for patients having neurologic and neuromuscular disorders - Aryen Kaushik; Anurag Bhatnagar; Taranjeet Kaur (Wolters Kluwer Medknow Publications, 2022)
This review provides an updated synopsis and documentation of various modified approaches for planning as well as fabricating removable prosthesis for patients suffering from commonly reported neurological and neuromuscular disorders. An increase in life expectancy and comparative decline in the number of newborns has led to a sharp growth in elderly population, a large number of which suffer from age-related disorders. Among these, neurological and neuromuscular disorders are the most common age-related diseases, which greatly affect the functioning as well as adaptability of any intraoral removable prosthesis. To address the above needs, a rich profusion of clinical reports have been published, which include modified conventional techniques of prosthesis fabrication, as per the symptoms and requirement of the patient. We included the Medline and Google database search using the mentioned keywords to congregate the literature.